Errors Use of Indonesian Language in Public Outdoor Media in Manado City - Ricky Gerungan; Djeinnie Imbang; Maya Pingkan Warouw (Universitas Muhammadiyah Enrekang, 2024)
The primary objective of this investigation is to scrutinize the utilization of the Indonesian language in outdoor media within Manado City, focusing on physical attributes, linguistic aspects, and the general application of the language in this specific context. Employing a qualitative research approach, the study centers its analysis on outdoor media installations situated in Manado, utilizing a sample size of 10 randomly selected images. The data collection process involves two main steps: firstly, gathering information on language usage in public spaces throughout Manado City, and subsequently, selecting ten data points that represent seven key aspects of Indonesian language prioritization. The findings of the study reveal two noteworthy outcomes: firstly, public space managers exhibit a preference for foreign languages over Indonesian in their language usage; and secondly, deviations from language rules are apparent, particularly in terms of spelling and word choice. The examination of Indonesian language use in outdoor media within Manado City indicates a presence of linguistic errors that defy established rules. Physically, there is a fusion of languages, comprising both Indonesian and foreign languages. While the language structure adheres to rules, imperfections persist in spelling and word selection. Despite these challenges, there is a positive trend in language typography, signaling an improvement in this specific aspect. In essence, the study underscores the existence of linguistic shortcomings in the public use of the Indonesian language in Manado City, encompassing discrepancies in language mixture, structural errors, and evolving typography practices